Do Rubber Floor Mats Prevent Lameness in Gestating Sows Housed in Large Groups? A Field Experiment on Three Commercial Farms in France - Adeline Huneau-Salaün; Stéphanie Bougeard; Loïc Balaine; Florent Eono; Éric Eveno; Maxime Guillermic; Rodolphe Thomas; Nicolas Rose; Françoise Pol (Animals, 2021)
Lameness and foot disorders are major health and welfare issues in intensive swine production systems. They are exacerbated when sows are housed in large groups on slatted concrete floors during gestation. Our study aimed to assess the effect of rubber mats in the lying area of the gestation pen on lameness and leg health in gestating sows housed in large pens in commercial conditions. The study was conducted on three commercial farms over two successive gestations. A total of 582 Large White × Landrace sows, housed in 10 static groups, were enrolled: 5 groups in pens with rubber mats and 5 groups on slatted concrete floors. Lameness, bursitis, leg injuries, claw growth defects and claw lesions were measured at the beginning, middle and end of each gestation period. The rubber mats decreased the risk of suffering from bursitis, but had no effect on the risk of lameness, leg injuries, claw growth defects or claw lesions. Sows housed on rubber mats were heavily soiled compared with those on slatted concrete floors because the mats were not perforated for slurry evacuation. Locomotion disorders and foot lesions remained prevalent despite the rubber mats in the lying area of the gestation pens, but adding rubber mats in service rooms and farrowing crates may produce better results.